Disaster relief ang preparedness: integrated marketing communication approach and disaster management in Kelantan flood prone area. - Haron, Mahmod Sabri (Universiti Sains Malaysia, 2016)
Flood is one of the most common natural disasters across the globe, jeopardising settlements along the floodplains and being considered a continued hazard for humanity. Malaysia is no exception due to its annual experience with flood during the monsoon season. Looking at the country's geographical location, most flood occurrences are natural resulting from the local tropical wet season that are characterised by heavy regular rainfall approximately during the period of October to March. The most recent incidence of flood disaster was considered the worst unexpected natural disaster in the country. Kelantan, Terengganu and Pahang were the three states which were hit the most, followed by Perak, Johor and Sabah.